A joint subcarrier selection and power allocation scheme using variational inequality in OFDM‐based cognitive relay networks. Issue 8 (4th March 2015) - Peng, Jun; Li, Shuo; Zhu, Chaoliang; Liu, Weirong; Zhu, Zhengfa; Lin, Kuo‐chi
Abstract: Introducing orthogonal frequency division multiplexing (OFDM) into cognitive radio (CR) can potentially increase the spectrum efficiency, but it also leads to further challenges for the resource allocation of CR networks. In OFDM‐based cognitive relay networks, two of the most significant research issues are subcarrier selection and power allocation. In this paper, a non‐cooperative game model is proposed to maximize the system throughput by jointly optimizing subcarrier selection and power allocation. First, taking the direct and relay links into consideration, an equivalent channel gain is presented to simplify the cooperative relay model into a non‐relay model. Then, a variational inequality method is utilized to prove the existence and uniqueness of the Nash equilibrium solution of the proposed non‐cooperative game. Moreover, to compute the solution of the game, a suboptimal algorithm based on the Lagrange function and distributed iterative water‐filling algorithm is proposed. The proposed algorithm can jointly optimize the process of subcarrier selection and power allocation. Finally, simulation results are shown to demonstrate the effectiveness of the proposed joint subcarrier selection and power allocation scheme. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper proposed a non‐cooperative game framework to maximize the system throughput by jointly optimizing subcarrier selection and power allocation. An equivalent channel gain is presented to simplify the cooperative relay model. And the variational inequality method is utilized to prove the existence and uniqueness of the Nash equilibrium solution. A suboptimal algorithm based on the Lagrange function and distributed iterative waterfilling algorithm is proposed to solve game, which can jointly optimize the process of subcarrier selection and power allocation.